(untitled) (The Pakistan Development Review, 1977)
The importance of cotton and its products for the economy of Pakistan is obvious enough. Cotton is the main cash crop of Pakistan. In fact, it is one-fourth of the value of the major crops of Pakistan and provides income to about 5 million people. It is a raw material for the textile industry which is die single largest industrial activity accounting for 48 % of the value-added of the large-scale manufacturing and 27% of its employment. The value of the installed textile machinery complex is around 15% of the total industrial investment in the country. Exports of cotton and its products constitute about a half of the total export proceeds of Pakistan. The final products of cotton, cloth and garments also play an important part in planning for a better standard of living in Pakistan. After food and shelter,1 this is the most essential item of consumption and hence adequate domestic availability of cloth assumes an important role in public policy. Cotton and its products have also been a major